A phase 1 randomized study assessing safety and immunogenicity of two 3-dose regimens of a Clostridium difficile vaccine in healthy older Japanese adults. Issue 19 (1st May 2019) - Inoue, Megumi; Yonemura, Takuma; de Solom, Richard; Yamaji, Masako; Aizawa, Masakazu; Knirsch, Charles; Pride, Michael W.; Jansen, Kathrin U.; Gruber, William; Webber, Chris
Highlights: Older Japanese adults received a toxoid based C difficile vaccine candidate. The vaccine was generally safe and well tolerated when given at 0, 1, and 6 months. Immune responses peaked at month 7 and remained elevated at month 12. Results support continued clinical evaluation of the C difficile vaccine candidate. Abstract: Background: Clostridium difficile infection (CDI) is a major global cause of nosocomial and community-acquired infections. Despite potentially severe or fatal complications and frequent recurrence, no preventive vaccine is currently available. This randomized, observer-blinded, placebo-controlled phase 1 study in older Japanese adults evaluated safety and immunogenicity of an investigational C difficile vaccine containing a mixture of genetically detoxified and chemically inactivated toxoids, A and B. Methods: Healthy Japanese adults aged 65 to 85 years were randomized in a 3:3:2 ratio to receive 100 or 200 μg of C difficile vaccine or placebo, respectively, at 0, 1, and 6 months (month regimen) or 1, 8, and 30 days (day regimen). The primary objective was safety evaluation. Vaccine immunogenicity, the secondary objective, was determined by assessing toxin A– and toxin B–specific neutralizing antibody levels in human sera. Results: Local reactions were reported by up to 33.3% of subjects per dose in the month regimen; percentages were generally higher in the 200-μg group. Such reactions were all mild or moderate in severity and generally transient. No adverse events in the month regimen led to subject withdrawal, and no serious adverse events were considered vaccine related. Further enrollment and dosing in the day regimen were discontinued after 3 subjects in the 100-μg group reported severe redness after dose 2. In the month regimen study arm, immune responses as measured by toxin-neutralizing antibody geometric mean concentrations, geometric mean fold rises, and proportions of subjects achieving prespecified fold rises were generally higher in the 200-μg group, peaked at month 7, and remained elevated at month 12. Conclusions: The C difficile vaccine candidate was safe, well tolerated, and immunogenic when administered to healthy older Japanese adults at 0, 1, and 6 months. Results support continued development of the vaccine for the prevention of CDI. ClinicalTrials.gov identifier: NCT02725437.